2021
DOI: 10.1016/j.annonc.2021.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Association of clinical factors and recent anticancer therapy with COVID-19 severity among patients with cancer: a report from the COVID-19 and Cancer Consortium

Abstract: Background Patients with cancer may be at high risk of adverse outcomes from SARS-CoV-2 infection. We analyzed a cohort of patients with cancer and COVID-19 reported to the COVID-19 and Cancer Consortium (CCC19) to identify prognostic clinical factors, including laboratory measurements and anti-cancer therapies. Patients and Methods Patients with active or historical cancer and a laboratory-confirmed SARS-CoV-2 diagnosis recorded between March 17-November 18, 2020 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
360
7
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(395 citation statements)
references
References 49 publications
21
360
7
7
Order By: Relevance
“…In our study eight patients with NEC were included and two of them were on platinum-etoposide. A recent publication of probably the largest series of cancer patients with COVID-19 reported that platinum-etoposide was one of the risk factors correlated with higher COVID-19 mortality rate 38 . Other studies have similarly reported worse outcomes in patients receiving cytotoxic chemotherapy 39 , 40 , but not all studies support that recent chemotherapy administration is associated with higher risk of death 12 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study eight patients with NEC were included and two of them were on platinum-etoposide. A recent publication of probably the largest series of cancer patients with COVID-19 reported that platinum-etoposide was one of the risk factors correlated with higher COVID-19 mortality rate 38 . Other studies have similarly reported worse outcomes in patients receiving cytotoxic chemotherapy 39 , 40 , but not all studies support that recent chemotherapy administration is associated with higher risk of death 12 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“… 40 In patients with cancer undergoing chemotherapy, COVID-19 disease severity was associated with either high or low lymphocyte counts, low platelet count, or high neutrophil count. 41 Since neutrophils likely play a role in COVID-19-related pulmonary damage, 14 42 reversal of neutropenia in patients with HM with active COVID-19 may not be advisable.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that about 40% of countries reported partial or complete disruptions of cancer treatment during the different peaks of the pandemic. 8 Compared to the general population, patients with cancer are more likely to be at high risk of serious COVID-19-related complications and mortality, 6,9 hence having information about e cacy of vaccine and optimal timing in relation to anti-cancer therapy to promote an effective immunity in this population remains crucial.…”
Section: Introductionmentioning
confidence: 99%